KORELASI KEMAMPUAN MENYIMAK DENGAN MENULIS PUISI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UMI - Ihramsari Akidah (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT The research aims to see a significant correlation between the ability to listen to poetry and the ability to write poetry for students of the Indonesian Language and Literature Study Program at the Faculty of Literature at the Muslim University of Indonesia (UMI).Research is an expose facto that is correlational, which consists of variable X that is the ability to listen to poetry as an independent variable and the Y variable the ability to write poetry as the dependent variable. In this study the population and sample were Pro students gram Stuin Indonesian Language and Literature, Faculty of Letters UMI in semester 3, as well as technique used to collect this research data is observation and test. Furthermore din this study, the data collected was analyzed using descriptive statistics of product moment correlation. The results of this study show that calculations using the product moment formula reach 0.08 because to find out whether or not there is significant correlation between listening ability and writing student poetry. So, it appears that the acquisition value of 0.08 (r xy arithmetic) <0.388 of (t value of the product moment table) at a significant level of 95% with the number of students 27 people. So, it needs to be emphasized that the high ability to listen to student poetry, less influence on his ability to write poetry. Keywords: Correlation, Listening to Poetry, Writing Poetry